Acute effects of pharmacological modifications of fatty acid metabolism on human satiety - Gatta, Blandine; Zuberbuehler, Christine; Arnold, Myrtha; Aubert, Roberte; Langhans, Wolfgang; Chapelot, Didier (British journal of nutrition, 2009)
The role of NEFA in eating behaviour is still poorly known. Our objective was to examine whether etomoxir (ETO), an inhibitor of NEFA oxidation, or ( − )-hydroxycitrate (HCA), an inhibitor of lipogenesis which may indirectly stimulate NEFA oxidation, alters satiety. Post-lunch satiety was measured in eight normal-weight male subjects who were deprived of time cues and received on three occasions either ETO (320 mg), HCA (2 g) or placebo (PLA) in random order. Between lunch and dinner, blood was withdrawn continuously and collected every 10 min for measures of plasma concentrations of glucose, insulin, lactate, TAG, NEFA, β-hydroxybutyrate (BHB), leptin and ghrelin. Results showed that HCA began to decrease hunger and desire to eat compared to PLA and ETO 210 min after lunch and increased satiety duration compared to PLA by 70 (se 23) min (P < 0·05), but did not modify energy intake at dinner. ETO did not affect any variable of satiety. HCA increased NEFA concentrations during the pre-dinner period, whereas ETO increased and decreased plasma concentrations of NEFA and BHB, respectively. Mean differences in plasma NEFA concentrations between HCA and PLA were predictive of the differences in satiety duration between treatments (r2 0·71, P < 0·01). Among treatments, plasma leptin concentration at dinner onset was the only blood variable correlated with energy intake at this meal (r − 0·75, P < 0·0005). In healthy, normal-weight men, acute HCA increased the intensity and duration of satiety possibly via increased NEFA disposal for oxidation.